RETRACTED ARTICLE: CYPA promotes the progression and metastasis of serous ovarian cancer (SOC) in vitro and in vivo - Zhi-Ying Qi; Fang Wang; Ying-Ying Yue; Xue-Wang Guo; Rui-Meng Guo; Hong-Lin Li; Yan-Ying Xu (BMC, 2019)
Abstract Ovarian cancer (OC) is a type of gynaecological malignancy with high mortality in females. Serous ovarian cancer (SOC) is a distinct subtype of OC with poor early diagnosis. Given the limitations of traditional therapies, such as chemotherapy, targeted treatment is therefore a promising therapy to improve the survival rate of SOC patients. Cyclophilin A (CYPA) is a member of Cyclophilin family and thought to participates in multiple cellular processes such as cell transduction and immune modulation. Recently, various of studies indicated that CYPA has critical impact on cancer progression. CYPA could regulate cell proliferation, invasion, and chemoresistance of multiple types of cancers. However, it is still unclear whether it could affect ovarian cancer. In this study, we demonstrated that CYPA was highly expressed in SOC tissues compared with adjacent tissues. Further, CYPA was significantly associated with clinical stage and lymphnode metastasis of SOC patients. Additionally, data indicated that knockdown of CYPA by its shRNA dramatically reduces migration and invasion capacity of SOC cells in vitro and blocks tumor metastasis in vivo. Our study investigates the involvement of CYPA in the progression and metastasis of SOC, and therefore provides CYPA as a promising therapeutic target for SOC treatment.